PEMBUATAN APLIKASI LAYANAN AKADEMIK UNTUK LEMBAGA PENDIDIKAN KURSUS MUGEN DENGAN CODEIGNITER (Information Technology and Telematics, 2013)
Non-formal education institutions or courses can be used as an alternative to learn the skills needed workforce. many emerging educational institutions courses (LPK) are organizing the work of education ready to meet the world's needs kerja.Lembaga education is a means to build community. Educational institutions can also be regarded as the reformer agent even change individual or group. Based on the purpose of education is expected to be able to create human beings who are able to face the challenges and changes globally and response positively. Objectives to be achieved is to build websites that can provide information media course information to the public. This research has resulted in the application of academic services to educational institutions with CodeIgniter Mugen course activities can facilitate the delivery of student information, student grades, subjects and teachers in educational institutions Mugen course using CodeIgniter. Keywords : Academic, LPK Mugen, CodeIgniter